Os determinantes empíricos da felicidade no Brasil The empirical determinants of happiness in Brazil - Raphael Bottura Corbi; Naércio Aquino Menezes-Filho (Brazilian Journal of Political Economy, 2006)
This paper investigates the role that economic variables play in the determination of happiness, using reported happiness as a proxy to individual well-being. We use microdata extracted from the World Values Survey for five countries, emphasizing the Brazilian case. Our findings suggest that there is a positive and significant correlation between happiness and income. Unemployment is also a large source of unhappiness. In most cases, happiness appears to be positively correlated to being married. Moreover, happiness is apparently U-shaped in age (minimizing at 50's).